A comparison of alcoholic pancreatitis in rat and man. Issue 5 (May 1971) - Sarles, H.; Lebreuil, G.; Tasso, F.; Figarella, C.; Clemente, F.; Devaux, M. A.; Fagonde, B.; Payan, H.
Abstract : Acute ethanol intoxication was studied in 38 Wistar rats, 18 on a balanced diet and 20 on a high fat diet, fed by gavage on 47% ethanol in a dosage of from 3 to 12 g/kg body weight daily for periods ranging from three to 16 days. No macroscopic changes in pancreas or liver were found in any of these animals. Histological changes (venous congestion of the pancreas, the liver, and the kidneys) were found in rats given 4 g or more per kilogram. The only difference between the findings in rats given a balanced diet and those given a high fat diet was the development of fatty livers in the latter group. Chronic ethanol intoxication was studied in 45 Wistar rats, on a balanced diet, which were given 20% ethanol freely for 20 to 30 months. More than half the animals developed pancreatic lesions very similar to those of human chronic pancreatitis. The pathological changes, in foci surrounded by normal pancreatic tissue, were a reduction in acini, duct multiplication (probably by neogenesis), protein plugs, sometimes calcified in the ducts and sclerosis. Samples of pancreatic juice from four animals exposed to ethanol contained significantly higher protein concentrations than samples taken from two control animals. Protein precipitates appeared spontaneously in the pancreatic juice of the animals exposed to ethanol, but not in that of the controls. These findings are very similar to those in alcoholic pancreatitis in man, which has thus been reproduced for the first time in experimental animals. Beta-cell adenomata of the islets of Langerhans were observed in four of the rats exposed to ethanol.